2012
DOI: 10.1002/aic.13917
|View full text |Cite
|
Sign up to set email alerts
|

3‐D full‐loop simulation of an industrial‐scale circulating fluidized‐bed boiler

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Three-dimensional (3-D) simulations using an Eulerian multiphase model were employed to explore flow behaviors in a full-loop industrial-scale CFB boiler with and without fluidized-bed heat exchanger (FBHE), where three solids phases were employed to roughly represent the polydisperse behavior of particles. First, a simulation of the boiler without FBHE is implemented to evaluate drag models, in terms of pressure profiles, mixing behaviors, radial velocity profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 23 publications
3
46
0
1
Order By: Relevance
“…In the bottom region of the riser, influenced by the one-side return of the bed material, the radial motion of solid phase shows a strong directionality. In the other region of the riser, the radial flux of solid phase mainly goes from core region to the near wall region, which is in accordance with the radial dispersion model of solid phase in literature (Lu et al, 2013;van der Meer et al, 2000). Moreover, it can be inferred that the internal circulation of solid phase exists at all the heights above the return system, which is in accordance with the radial motion of solid phase reported by Nikolopoulos et al (2013) and Rhodes et al (1998).…”
Section: Distribution Property Of Solid Velocitysupporting
confidence: 88%
See 1 more Smart Citation
“…In the bottom region of the riser, influenced by the one-side return of the bed material, the radial motion of solid phase shows a strong directionality. In the other region of the riser, the radial flux of solid phase mainly goes from core region to the near wall region, which is in accordance with the radial dispersion model of solid phase in literature (Lu et al, 2013;van der Meer et al, 2000). Moreover, it can be inferred that the internal circulation of solid phase exists at all the heights above the return system, which is in accordance with the radial motion of solid phase reported by Nikolopoulos et al (2013) and Rhodes et al (1998).…”
Section: Distribution Property Of Solid Velocitysupporting
confidence: 88%
“…Nikolopoulos et al (2013) reported the full-loop isothermal simulation of the hydrodynamics in a CFB reactor by means of TFM. Using an Eulerian multiphase model, Lu et al (2013) investigated the hydrodynamic behaviors of gas and solid phases in an industrial-scale CFB boiler with and without fluidized bed heat exchanger.…”
mentioning
confidence: 99%
“…Computational Fluid Dynamics (CFD) based on the Euler-Euler method has been successfully applied to investigate the micro-structure of gas and solids flow [22] , heat transfer performance and operation optimization of industrial processes [23,24] . For bed-to-wall heat transfer, most of investigators focused on the predicting ability of the model on the heat transfer coefficient near the hot wall or the effect of bubble movement on heat transfer coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…The EMMS drag model has now been applied widely because of its effectiveness at upgrading CFD. Extensive studies has been carried out at our institute by validating the model via simulations of the various aspects of the hydrodynamics of lab and pilot scale CFB units [38,39,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], studying its relationship with classical continuum models and therefore formulating structure-dependent continuum models [56][57][58][59][60], doing various industrial projects [61][62][63][64][65][66][67][68] and extending the model to (i) consider the effect of heat and mass transfer as well as chemical reaction [69][70][71][72][73], (ii) consider the effect of particle size distribution [74,75], (iii) simulate the hydrodynamics of bubbling and turbulent fluidization [76][77][78][79] and (iv) the gas-liquid and gas-liquid-solid systems [40,[80][81]…”
mentioning
confidence: 99%